A small three-way valve using particle excitation with piezoelectric transducers for hydraulic actuators. (3rd May 2018) - Osaki, Hayato; Kanda, Takefumi; Ofuji, Shoki; Seno, Norihisa; Suzumori, Koichi; Ukida, Takahiro; Nabae, Hiroyuki
Abstract: Robots composed of hydraulic actuators have been utilized in various fields and at disaster sites. However, the hydraulic control system for multiple-degree-of-freedom mechanisms is large because such systems require many control components. The purpose of this research was to develop a small hydraulic flow control valve. This paper describes the fabrication and evaluation of a small three-way valve by particle excitation using a piezoelectric transducer. This valve consists of two transducers and can switch the inlet and outlet ports by applying an AC voltage of different driving frequencies to each transducer because each transducer has different resonant frequencies. The flow rate was controlled by applying a voltage to the piezoelectric transducer. We evaluated the vibration characteristics of the fabricated three-way valve. The vibration velocity exhibited peaks at 120 and 155 kHz for the inlet and outlet port, respectively, and that of each transducer increased with the applied voltage. Therefore, this three-way valve can switch the opening port by changing the driving frequencies and continuously controlling the flow rate. As a result, we have succeeded in driving the novel small three-way valve. Abstract :